Exploring the prevalence of atopic disease among adult cancer survivors: insights from the 2021 NHIS - Lu Xiao; Yuhui Shen; Nana Xiang; Juebo Yu (PLoS ONE, 2025)
Cancer survivors who undergo radiotherapy, immunotherapy, and chemotherapy experience a decline in immune system function. Atopic diseases (ADs) are associated with systemic immunosuppressant medications and exposure to environmental allergens. However, the relationship between cancer survivorship and the prevalence of ADs remains poorly understood. This study investigated whether the prevalence of ADs is increased among cancer survivors. A cross-sectional survey was conducted using data from the 2021 US National Health Interview Survey (NHIS). The data were on 28,617 adults aged 18 years and older. Data analysis was performed between May 11, 2024, and July 30, 2024. The NHIS participants reported whether they had a history of current hay fever, still asthma, current skin allergy, and/or current food allergy. A history of cancer was defined on the basis of self-reported data from the NHIS. The weighted prevalence and 95% confidence intervals (CIs) of ADs were calculated. Comparisons of AD prevalence between cancer survivors and the general population were conducted using chi-square tests and multiadjusted logistic regression models. Of the 28,617 adults sampled in the 2021 NHIS, the prevalence of ADs among the cancer survivors was as follows: current hay fever (54.5%; 95% CI, 52.6%–56.4%), persistent asthma (14.7%; 95% CI, 12.9%–13.9%), current skin allergy (13.6%; 95% CI, 10.1%–15.0%), and current food allergy (11.2%; 95% CI, 10.0%–12.4%). In multivariable logistic regression models adjusted for age, sex, race/ethnicity, family income, educational level, insurance status, body mass index, general health status, region, location, and comorbidity burden, the cancer survivors had significantly higher odds of ADs than did the general population. In particular, they had higher odds of current hay fever (aOR, 1.14; 95% CI, 1.05–1.23), persistent asthma (aOR, 1.17; 95% CI, 1.03–1.33), current skin allergy (aOR, 1.26; 95% CI, 1.13–1.41), and current food allergy (aOR, 1.22; 95% CI, 1.08–1.38). The findings of this cross-sectional study indicated that the prevalence of ADs was significantly higher in cancer survivors than in the general population. Future research is required to elucidate the underlying mechanisms, optimize treatment strategies, and enhance the overall well-being of individuals with ADs and a history of cancer.